2019
DOI: 10.1186/s13104-019-4583-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of neonatal danger signs, care seeking practice and associated factors among postpartum mothers at public health facilities in Ambo town, Central Ethiopia

Abstract: Objective Neonatal mortality has remained high in Ethiopia inspite of different efforts being undertaken to reduce this negative trend. Early detection of neonatal illnesses has an important step towards improving newborn survival. Toward this end, there is a need for postpartum mothers to be able to identify signs in neonates that signifies severe neonatal illnesses. There is limited information about the knowledge of post-partum mothers on NDSs and associated factors in the study area. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 17 publications
7
55
3
Order By: Relevance
“…Mother's educational status, most recent baby developed danger signs, exposure to media, higher parity, birth preparedness, mother's decision-making power and husband involvement in MNCH were significant predictors of mother's knowledge of neonatal danger signs and healthcare-seeking for NDS. We found that mother's knowledge of neonatal danger signs was 36.5%, which was higher than findings from previous researches conducted in Ghana, 34 Nigeria, 35 Kenya, 36 Uganda 20 and similar studies elsewhere in Ethiopia including Wolkite, 10 Ambo, 17 Gondar, 22 and Woldia towns. 9 This discrepancy might be due to differences in the study period, socio-cultural characteristics, study setting and defining the outcome variable.…”
Section: Mother's Knowledge Of Neonatal Danger Signs and Health-seekicontrasting
confidence: 85%
See 3 more Smart Citations
“…Mother's educational status, most recent baby developed danger signs, exposure to media, higher parity, birth preparedness, mother's decision-making power and husband involvement in MNCH were significant predictors of mother's knowledge of neonatal danger signs and healthcare-seeking for NDS. We found that mother's knowledge of neonatal danger signs was 36.5%, which was higher than findings from previous researches conducted in Ghana, 34 Nigeria, 35 Kenya, 36 Uganda 20 and similar studies elsewhere in Ethiopia including Wolkite, 10 Ambo, 17 Gondar, 22 and Woldia towns. 9 This discrepancy might be due to differences in the study period, socio-cultural characteristics, study setting and defining the outcome variable.…”
Section: Mother's Knowledge Of Neonatal Danger Signs and Health-seekicontrasting
confidence: 85%
“…Mothers who were able to mention at least 3 neonatal danger signs among the 12 neonatal danger signs without prompt. 10,17,21 Appropriate Health-Seeking Practices Mothers who sought care for neonatal danger signs from well-qualified health professionals in governmental and/or private health facilities. 27,28 Inappropriate Health-Seeking Practices Mothers who sought care for neonatal danger signs other than qualified health professionals like purchasing over the counter drugs, treating by home remedies, seeking care from temples and traditional healers.…”
Section: Measurements Good Knowledge Of Neonatal Danger Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across contexts, recognition of neonatal danger signs are often proposed as a determinant of the types of care methods sought as well as care timeliness [6,23,28]. Symptoms that indicated illness among parental figures most often included fever, lack of breastfeeding and excessive or abnormal crying.…”
Section: Discussionmentioning
confidence: 99%